Preschool teachers' beliefs about and instruction for writing. Issue 4 (2nd October 2019) - Gerde, Hope K.; Wright, Tanya S.; Bingham, Gary E.
ABSTRACT: Early writing—a valuable early literacy skill—begins to develop prior to kindergarten. Young children participating in preschool benefit from writing opportunities facilitated by teachers. Writing opportunities, however, are often limited in preschool settings. It is important to understand teachers' beliefs and practices for promoting early writing, because teachers' beliefs inform their practices of this valuable skill. Thus, this study examined ways in which preschool teachers talk about and enact practices to support children's writing. Thirty-two preschool teachers participated in structured interviews about their beliefs and practices for promoting writing and were observed using the Writing Resources and Interactions in Teaching Environments assessment to examine reported and observed practices. Qualitative coding organized teachers' interview responses into conceptually meaningful categories. Results indicated that teachers' reported and observed practices generally aligned but represented a limited set of pedagogical approaches. Although teachers reported and were observed providing materials and enacting strategies for guiding children's handwriting, few identified strategies to support children in writing for meaning (i.e., composing) or in a manner that supported other literacy skills (e.g., letter-sound knowledge). Programmatic structure, curriculum, and teachers' background characteristics were not associated with teachers' beliefs or practices.